Control and the Health Effects of Work–Family Conflict: A Longitudinal Test of Generalized Versus Specific Stress Buffering. (September 2020) - Badawy, Philip; Schieman, Scott
The stress associated with work-to-family conflict (WFC) and family-to-work conflict (FWC) is well documented. However, surprisingly little is known about the resources that moderate the effects of work–family conflict on health over time. Using four waves of panel data from the Canadian Work, Stress, and Health Study (2011–2017; n = 11, 349 person-wave observations), we compare how a core psychosocial resource (personal mastery) and a salient organizationally based resource (schedule control) moderate the health effects of WFC and FWC. After establishing these health effects related to distress and physical symptoms, we discover that mastery has generalized stress-buffering functions whereby it alleviates the health effects of both WFC and FWC. In contrast, schedule control has asymmetrical moderating functions: It attenuates the health effects of WFC only. These findings elaborate and sharpen the scope of resources as moderators in the stress process model—and we integrate these ideas with other conceptual models like the job demands-resources model.